Impact of premium collection on investment pattern of Nepalese life insurance companies - Upadhyay, Jitendra Prasad; Dhaugoda, Rumita (NCC Journal, 2021)
The premium collection is one of the main sources for investment and measuring profitability of insurance companies. This research aims to analyze the effect of premium collection on the investment strategy and profitability of the life insurance company. Only four insurance companies have been selected out of the nineteen life insurance companies in Nepal using simple random sampling technique. The purpose of this descriptive and causal-comparative study is to examine the impact of premium collection on investment and profitability in life insurance companies. Both primary and secondary data have been incorporated. Descriptive statistical tools consist of mean, standard deviation, coefficient of variation as well as the inferential statistic consists of correlation and regression analysis as secondary data variables. The findings indicate a positive and significant relationship between total investment and premium collection in the life insurance industry. Additionally, premium collection shows significantly positive relationships with earnings per share and net profit. However, the research also suggests an insignificant relationship between premium collection and return on assets (ROA) and return on equity (ROE). Furthermore, the study highlights the influence of various other factors on premium collection and investment patterns, including firm size, government regulations, investment duration, investment period, and investment objectives. Understanding these factors can aid in formulating an effective structure for premium collection and investment strategies to achieve higher profitability. The research findings shed light on the significance of premium collection in guiding investment decisions in the life insurance sector. The findings of this study can contribute to the formulation of effective premium collection and investment strategies to maximize profits in this industry.